On some new N-independent-variable discrete inequalities of the Gronwall type - En Hao Yang (International Journal of Mathematics and Mathematical Sciences)
In this paper we shall establish some new discrete inequalities of the Gronwall type in N-independent variables. They will have many applications for finite difference equations involving several independent variables and for numerical analysis. Their consequence for the case of N=3, generalizes all of the known theorems obtained by Pachpatte and Singare in [1]. An example, to which those results established in [1] are inapplicable, is given here to convey the usefulness of the results obtained.